2022
DOI: 10.1371/journal.pone.0264135
|View full text |Cite
|
Sign up to set email alerts
|

Do business records management affect business growth?

Abstract: The implementation of a records management plan is an excellent approach to ensure small and medium-sized enterprises (SMEs) are sustained and continue to expand into huge or multi-national corporations. Maintaining records helps businesses in making better judgments and developing appropriate policies, resulting in enhanced effectiveness and efficiency. This will leverage means for tracking business progress and making appropriate decisions to expand the productive component of the economy. SMEs Business grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…Several studies examining the connection between entrepreneurial Orientation and organizational success have produced substantial results in association with business growth and performance (Clement, Huaicheo et al, 2021;Adam, Fuzi et al, 2022;Mintah, Gabir et al, 2022). Most discoveries from such studies have found a substantial and favourable entrepreneurial orientation-innovation nexus.…”
Section: Literature Review and Related Theoretical Basismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies examining the connection between entrepreneurial Orientation and organizational success have produced substantial results in association with business growth and performance (Clement, Huaicheo et al, 2021;Adam, Fuzi et al, 2022;Mintah, Gabir et al, 2022). Most discoveries from such studies have found a substantial and favourable entrepreneurial orientation-innovation nexus.…”
Section: Literature Review and Related Theoretical Basismentioning
confidence: 99%
“…Many scholars have given appraisal as to the efficiency of SEM-PLS software in quantitative analysis works. According to Sarstedt and Cheah (2019), this software is now regarded as one of the best options for partial least squares structural equation modeling (SEM) as supported by (Mintah, Gabir et al, 2022). The PLS-SEM enables the development of a theory-based research paradigm by transforming theories and concepts into unmeasured variables (latent) and practical notions into measurements (Hair, Hult et al, 2017;Cheah, Sarstedt et al, 2018).…”
Section: Analytical Approachmentioning
confidence: 99%
“…Having established this, it is clear that the relationship between government policies, SSE progress, SSE expansion and promotion, growth and performance, remains a crucial subject in need of further investigation for growing our business (Gundry & Welsch, 2001). Growing and sustaining these small scale enterprise help create employment, reduce poverty and generates revenue for the government as supported by (Abor & Quartey, 2010;Amoah & Amoah, 2018;Mintah et al, 2022;Turner et al, 2016). Hence, the business sector requires specific knowledge, innovative strategies, and knowledge management to ease businesses from failing and continue to perform and satisfy the needs of society (Clement et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Kendala dalam pencatatan akuntansi yang mempengaruhi dalam mempraktikan akuntansi dan penyusunan laporan keuangan ini sejalan dengan hasil penelitian terdahulu. (Herieli & Rimisho, 2019;Mintah et al, 2022;Sanga et al, 2014).…”
Section: Kendala Yang Menghambat Umkm Binaan Rumah Umkm Kabupaten Bar...unclassified